A 3.0-7.5 GHz CMOS UWB PA for group 1∼3 MB-OFDM application using current-reused and shunt-shunt feedback - Sohiful Anuar, Zainol Murad; Pokharel, R. K; Kanaya, H.; Yoshida, K. (IEEE, 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/